No hope for Pyrenean glaciers - Juan Ignacio López-Moreno; Jesús Revuelto; Eñaut Izagirre; Esteban Alonso-González; Ixeia Vidaller; Josep Bonsoms (Annals of Glaciology, 2025)
Updated estimates of 2024 ice thickness, the surface elevation losses in the last years and simulations of mass balance and evolution (using the Instructed Glacier Model) for the three largest Pyrenean glaciers strongly suggest that by 2034 the Pyrenees will be ice-free. If extreme summers like 2022 and 2023 recur, this could happen even earlier. We show that by 2030, 94% (from 0.22 to 0.01 km2) of the ice in Monte Perdido, 91% (from 0.22 to 0.05 km2) of the ice in Ossoue and 79% of the ice in Aneto (from 0.34 to 0.06 km2) will have melted under the RCP4.5 scenario; these numbers are 83%, 72% and 57% under a committed ice loss scenario, meaning that only 0.05, 0.12 and 0.12 km2 of ice will remain, respectively. In 2034, most likely they will have completely disappeared under the three considered scenarios (RCP 4.5, ‘committed ice loss’ and extreme 2022 year in a loop). The loss of these glaciers is a harbinger for what will happen in many other mountain regions.